Cardiomyocytes Methods and Protocols - Skuse, Gary R.; Skuse, Gary R.; Ferran, Maureen C.; Ferran, Maureen C. (Methods in Molecular Biology, 2015)
This volume has been assembled for scientists interested in basic and applied biomedical research directed toward understanding the development, genetics, and function of cardiomyocytes.  The methods and protocols contained within it address cell culture techniques, cardiomyocyte differentiation and redifferentiation, experimental induction of cardiomyopathies, introducing genes into cardiomyocytes, genomic approaches to the understanding cardiomyocytes, cryopreservation of neonatal cardiomyocytes, and modeling of cardiomyocyte function. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Practical and current, Cardiomyocytes: Methods and Protocols explores complimentary areas of cardiomyocyte science that, taken together, can inform individuals with a broad range of interests.